1987
DOI: 10.1039/dt9870002379
|View full text |Cite
|
Sign up to set email alerts
|

Metal(II) hexafluoroantimonates: preparation and characterization of MF2·2SbF5(M = Mg, Ni, Zn, Fe, Co, Cu, Cr, Ag, Cd, or Pb) and the X-ray structure determination of AgF2·2SbF5

Abstract: an hydrous H F or SO, at room temperature give adducts of composition M F2-2SbF,. Efforts to prepare similar adducts of the difluorides of Ca, Sr, and Ba led only to non-stoicheiometric compounds. Vibrational spectra and X-ray powder diffraction studies indicate that the Mg, Ni, and Zn compounds and the Fe, Co, and Cu compounds form two distinct isostructural triads. The remaining adducts have structures which differ from each other and from those of the two triads. A single-crystal X-ray study on AgF2*2SbF, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
89
0
2

Year Published

1987
1987
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(96 citation statements)
references
References 1 publication
(1 reference statement)
5
89
0
2
Order By: Relevance
“…The X-ray diffraction study had revealed a true Ag2+ ion in a distorted octahedral environment (14). However, the course of the solvolysis and the final product are surprising.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The X-ray diffraction study had revealed a true Ag2+ ion in a distorted octahedral environment (14). However, the course of the solvolysis and the final product are surprising.…”
Section: Resultsmentioning
confidence: 99%
“…Both Ni(SbF6)2 (11,12,14) and Sn(SbF6), (13) Alternate routes to P-Ag(SbF6)2: (a) 0.323 g of AgSbF6 is allowed to react with an excess of S2O6F2 at room temperature. The white color of AgSbF6 changes immediately to black-brown. '…”
Section: Physical Properties and Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…The AsF 6 ions are close to octahedral; the single non-bridging F(3) atom is closer 11.677 (7) A] than the remainder, which span the range 1.714 (4)-1.729 (6) A. The structure of AgFE.ASF 5 is very different from that of AgF 2 itself (Fischer, Schwarzenbach & Rietveld, 1971) and from that of AgFE.2SbF 5 (Gantar, Leban, Holloway & Frlec, 1987), in both of which the coordination around the Ag atom is probably best regarded as square planar. The average bond length of the Ag-F bonds in the square plane about Ag in AgF2.2SbF 5 [2.114 (5) A] is a little longer than the equivalent in AgF 2 [2.071 (6)AI.…”
Section: Introductionmentioning
confidence: 88%